Expresión yz∨¬x¬y
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
(y∧z)∨(¬x∧¬y)
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 1 |
+---+---+---+--------+
| 0 | 0 | 1 | 1 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 0 |
+---+---+---+--------+
| 1 | 1 | 1 | 1 |
+---+---+---+--------+
Ya está reducido a FND
(y∧z)∨(¬x∧¬y)
(y∨¬x)∧(y∨¬y)∧(z∨¬x)∧(z∨¬y)
(y∨(¬x))∧(y∨(¬y))∧(z∨(¬x))∧(z∨(¬y))
(y∨¬x)∧(z∨¬y)
(y∧z)∨(¬x∧¬y)